Functionalized 2D Clay Derivative: Hybrid Nanosheets with Unique Lead Sorption Behaviors and Interface Structure. Issue 4 (24th November 2017) - Yan, Zhaoli; Fu, Liangjie; Yang, Huaming
Abstract: Clay mineral and its derivatives can play an important role in stabilizing functional‐groups and nanostructures. Here, a TP‐SiNSs (TiSi2 O5 (OH)2 ·(OH2 )2 ) nanocomposite, with highly dispersed and stabilized TiO2 precursor (TP, Ti(OH)4 gel) on template‐free 2D silica nanosheets (SiNSs, Si2 O3 (OH)2 ), is presented, which is derived from kaolinite, a natural 2D layer mineral. Unique lead sorption behaviors are observed for balanced hydrophobicity–hydrophilicity, short sorption equilibrium time (within 5 min), large applied sorption capacities (≈38 000 kg polluted drinking water per kg TP‐SiNSs, effluent Pb(II) contents <10 µg L −1 ), and excellent renewability. The highly dispersed surface titanium hydroxyl groups, together with 2D hierarchical porous nanostructure of TP‐SiNSs effectively facilitate the selective adsorption of Pb(II) ions, inhibit the pore blockage after Pb(II) adsorption, and prolong the service life. The detailed adsorption mechanism as a function of pH value and ion concentration is clarified by density functional theory (DFT) calculations, and the higher adsorption selectivity of TP‐SiNSs for Pb(II) over Ca(II) and Mg(II) is attributed to surface complex on TP‐SiNSs, which induces strong bonding between Pb(II) and titanium hydroxyl groups. The interface geometry and electronic structure calculations demonstrate that the stabilized and spatially distributed titanium hydroxyl group on TP‐SiNSs can greatly enhance the surface adsorption ability. Abstract : Highly stabilized TiO2 precursor (TP) functionalized 2D silica nanosheets (SiNSs) hybrid exhibits unique lead sorption behaviors. Well dispersed surface titanium hydroxyl groups and 2D hierarchical porous nanostructure of TP‐SiNSs effectively facilitate the selective adsorption of Pb(II) ions, and the stabilized and spatially distributed titanium hydroxyl group on TP‐SiNSs can greatly enhance the surface adsorption ability.